Pompoms ; Pik Pak Pow ; Matters of movement [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1989)
A second look at the pedophile situation in Pagsanjan. Focuses on action films. Two dancers, Elizabeth Roxas and Stephen Smith talk about their craft as artist in modern form.
Pompoms (15 min.) -- Pik Pak Pow (12 min.) -- Matters of movement (12 min.)
VHS.
Keywords: Roxas, Elizabeth; Smith, Stephen; Ballet dancing; Motion picture producers and directors -- Philippines -- Interviews; Motion pictures -- Production and direction -- Philippines; Pedophilia -- Philippines -- Pagsanjan (Laguna)